Physiological, nutritional, and molecular responses of Brazilian sugarcane cultivars under stress by aluminum - Mariane de Souza Oliveira; Sâmara Vieira Rocha; Vanessa Karine Schneider; Flavio Henrique-Silva; Marcio Roberto Soares; Andrea Soares-Costa (PeerJ, 2021)
Background Sugarcane is a crop of global importance and has been expanding to areas with soils containing high levels of exchangeable aluminum (Al), which is a limiting factor for crop development in acidic soils. The study of the sugarcane physiological and nutritional behavior together with patterns of gene expression in response to Al stress may provide a basis for effective strategies to increase crop productivity in acidic soils. Methods Sugarcane cultivars were evaluated for physiological parameters (photosynthesis, stomatal conductance, and transpiration), nutrient (N, P, K, Ca, Mg, and S) and Al contents in leaves and roots and gene expression, of the genes MDH, SDH by qPCR, both related to the production of organic acids, and SOD, related to oxidative stress. Results Brazilian sugarcane RB867515, RB928064, and RB935744 cultivars exhibited very different responses to induced stress by Al. Exposure to Al caused up-regulation (SOD and MDH) or down-regulation (SDH, MDH, and SOD), depending on the cultivar, Al level, and plant tissue. The RB867515 cultivar was the most Al-tolerant, showing no decline of nutrient content in plant tissue, photosynthesis, transpiration, and stomatal conductance after exposure to Al; it exhibited the highest Al content in the roots, and showed important MDH and SOD gene expression in the roots. RB928064 only showed low expression of SOD in roots and leaves, while RB935744 showed important expression of the SOD gene only in the leaves. Sugarcane cultivars were classified in the following descending Al-tolerance order: RB867515 > RB928064 = RB935744. These results may contribute to the obtention of Al-tolerant cultivars that can play their genetic potential in soils of low fertility and with low demand for agricultural inputs; the selection of potential plants for breeding programs; the elucidation of Al detoxification mechanisms employed by sugarcane cultivars.